In‐house–validated liquid chromatography–tandem mass spectrometry (LC‐MS/MS) method for survey of acrylamide in various processed foods from Korean market. Issue 5 (28th August 2013) - Lee, Sanghee; Yoo, Miyoung; Koo, Minseon; Kim, Hyun Jung; Kim, Meehye; Park, Sung‐Kug; Shin, Dongbin
Abstract Acrylamide (AA) is a chemical found in starchy foods that have been cooked at high temperatures. The objective of this study is to monitor the levels of AA in a total of 274 samples of potato chips, chips (except potato chips), biscuits, French fries, breakfast cereals, chocolate products, tea, seasoned laver, and nut products sampled in Korean market. These processed foods include (1) potato chips, (2) chips (except potato chips), (3) biscuits, (4) French fries, (5) breakfast cereals, (6) chocolate products, (7) tea, (8) seasoned laver, and (9) nut products. Samples used for this study were cleaned up using HLB Oasis polymeric and Accucat mixed‐mode anion and cation exchange solid‐phase extraction cartridge. Liquid chromatography–tandem mass spectroscopy (LC‐MS/MS) was validated in‐house as an efficient analytical method for the routine analysis of AA in various food products. AA was detected with a Fortis dC18 (1.7 μm, 100 mm × 2.1 mm) column using 0.5% methanol/0.1% acetic acid in water as the mobile phase. Good results were obtained with respect to repeatability (RSDs < 5%). The recoveries obtained for a variety of food matrices ranged between 94.5% and 107.6%. Quantification during routine monitoring was sensitive enough to detect AA at a concentration of 10 μg/kg. A total of 274 food samples were analyzed for AA. The AA levels in the food groups were in the following order: potato chips > French fries > biscuits > tea > chips (except potato chips) > seasoned laver > breakfast cereals > chocolate products > nut products. AA was detected at levels ranging from not detectable to 1435 μg/kg.